Factors That Promote Innovativeness and Being An Innovative Learner At Work – Results From PIAAC. (5th May 2016) - Anne Støren, Liv
Abstract : In this article, innovative activity is considered in the light of broader conceptualisations of innovativeness and what it means to be innovative. Central to the definition of innovativeness used in the analysis is that the worker actively seeks new knowledge and uses it for work‐related tasks. This is based on previous research emphasising learning‐by‐doing, taking new knowledge into use and learning organisations. Innovativeness is analysed for Denmark, Finland, The Netherlands and Norway. Data from the PIAAC survey of adult skills are examined to identify key factors involved in promoting innovative behaviours at work. Significant country differences are found. Findings suggest that the work profiles of the workers, the work environment and the intensity of training and learning are very important for the innovative capabilities of the workforce.